ENT300 Rainbow Muslim's Collection / Dygku Nur Syahierah Awg Dzulkarnain... [et.al] - Awg Dzulkarnain, Dygku Nur Syahierah; Nizam, Nur Ainni; Gornsen, Brenda; Haris, Khairul Anwar; Shukor, Nurul Fazira (2014)
The name of the company is Rainbow Muslim's Collection The location of this business is Level 2, Kompleks Islam Sarawak, Jalan P Ramlee 93050 Kuching, Malaysia. We choose this location because it is a shopping mall that situated in the center area of people passage from every place in Kuching. Besides, most of people that come to this shopping mall are muslim. The business is in the form of partnerships, which consists of five members. Each partner contributes certain amounts of cash as agreed in the partnership agreement. According to our planned, we will start our business on 1st January 2015. This business provides colourful shawls with various styles, jubbah and telekung that we ensure will meet the customer's satisfaction. Besides to gain maximum profit, the aim of this business is to provide the silk, comfortable, and stylish shawl, jubah and telekung for the customers to fulfil customer satisfaction, requirement and needed. The customers also may choose and pick any colour of our products that they want since this business producing various colours of shawl, jubah and telekung that will meet their satisfaction. All partners are entitled to participate in the business management. We have agreed that Dygku Nur Syahierah bt Awg Dzulkarnain as the General Manager, Brenda Ak Gornsen as Administration Manager, Khairul Anuar b Haris as the Operational Manager, Nur Ainni binti Nizam as the Marketing Manager and Nurul Fazira bt Shukor as the Financial Manager. The General Manager is responsible in planning organizing, leading and controlling of the entire business. The company is led by Miss Dygku Nur Syahierah. She is the owner and the main head of the company. As the Administration Manager, Miss Brenda is the one who responsible for the entire jobs related to the administration. The third member is the one who control and monitor the operation of our business which is the Operational Manager. As the Operational Manager, Mr.Khairul will manage the services that the company wanted to provide to the customers. Miss Nur Ainni will responsible in preparing marketing plan as she is the Marketing Manager. This is includes identifying the target market share, develop sales forecast and develop market strategies. The last member is Financial Manager, Miss Nurul Fazira who will take responsibility in managing financial of the company. She will monitor and control the expenditure that has been by used the company. Every profit that been gain will be written in the company profit account. The profits and losses will be written in the expenditure account. We have 7 workers consist of General Manager, Administration Manager, Operational Manager, Marketing Manager and Financial Manager to run this business. Our business will operate from Monday to Thursday from 10.00am until 10.00pm and on Friday to Sunday we will start operate from 10:00am until 11:00pm. We also run e-business to attract more customers that living in another place. We put postages for online buyers and we will deliver our products as soon as possible as the customer requirement. We will ensure that we provide the best services for our customers.